Efficacy of concurrent radiotherapy in patients with locally advanced rectal cancer and synchronous metastasis receiving systemic therapy - Yin, Tzu-Chieh; Chen, Po-Jung; Yeh, Yung-Sung; Li, Ching-Chun; Chen, Yen-Cheng; Su, Wei-Chih; Chang, Tsung-Kun; Huang, Ching-Wen; Huang, Chun-Ming; Tsai, Hsiang-Lin; Wang, Jaw-Yuan (Frontiers in Oncology, 2023)
Background: Neoadjuvant chemoradiotherapy followed by total mesorectal excision is the standard treatment for patients with nonmetastatic locally advanced rectal cancer (LARC). However, for patients with LARC and synchronous metastasis, the optimal treatment strategy and sequence remain inconclusive. In the present study, we evaluated the efficacy and safety of concurrent radiotherapy in patients with de novo metastatic rectal cancer who received chemotherapy and targeted therapy. Methods: We retrospectively reviewed the data of 63 patients with LARC and synchronous metastasis who received intensive therapy at the study hospital between April 2015 and November 2018. The included patients were divided into two groups: RT-CT, those who received systemic chemotherapy with targeted therapy and concurrent radiotherapy (for primary rectal cancer), and CT, those who received only systemic chemotherapy with targeted therapy. Results: Treatment response was better in the RT-CT group than in the CT group. The rate of primary tumor resection (PTR) was higher in the RT-CT group than in the CT group (71.4% and 42.9%, respectively; P = .0286). The RT-CT group exhibited considerably longer local recurrence-free survival (P = .0453) and progression-free survival (PFS; from 13.3 to 22.5 months) than did the CT group (P = .0091); however, the groups did not differ in terms of overall survival (OS; P = .49). Adverse events were almost similar between the groups, except frequent diarrhea, the prevalence of which was higher in the RT-CT group than in the CT group (59.5% and 23.8%, respectively; P = .0075). Conclusions: In the era of biologics, radiotherapy may increase the resectability of primary rectal tumors, reducing the risk of locoregional failure and prolonging PFS. Concurrent pelvic radiotherapy may not substantially improve OS, which is indicated by metastasis. Hence, the resection of the distant metastases may be essential for improving long-term OS. To further determine the efficacy of concurrent radiotherapy, additional prospective, randomized studies must combine preoperative pelvic radiotherapy with PTR and metastectomy to treat patients with stage IV LARC.